2017
DOI: 10.1159/000479341
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postoperative Non-Chylous Massive Discharge after Pancreaticoduodenectomy for Pancreatic Ductal Adenocarcinoma

Abstract: Background: Pancreaticoduodenectomy (PD) is performed for pancreatic ductal adenocarcinoma (PDA) located at the pancreas head/body. Non-chylous massive discharge after PD is frequently encountered and can cause a vicious cycle of complications associated with severe dehydration and protein loss. Methods: From August 2008 to June 2015, 102 patients who underwent PD for PDA were retrospectively reviewed. High non-chylous discharge was defined as postoperative daily serous discharge exceeding 10 mL/kg. Predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The early detection of CR-CL helps shorten the postoperative hospital stay and reduce medical costs, as conservative treatment is effective [11,28]. In addition, as in previous studies [13,14], we also showed that a high DOV was associated with significant protein loss. This protein loss causes a decrease in the plasma osmolality and may increase transudative ascites, creating a vicious cycle that may increase the DOV.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The early detection of CR-CL helps shorten the postoperative hospital stay and reduce medical costs, as conservative treatment is effective [11,28]. In addition, as in previous studies [13,14], we also showed that a high DOV was associated with significant protein loss. This protein loss causes a decrease in the plasma osmolality and may increase transudative ascites, creating a vicious cycle that may increase the DOV.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the above, we newly showed that a low DOV on POD 1 (< 227 ml) was a potential postoperative warning sign of CR-POPF. Ito et al reported that the CR-POPF was significantly lower in patients with a high DOV (DOV > 10 ml/kg/day) than in those with a low DOV (DOV ≤ 10 ml/kg/day) after PD for pancreatic ductal adenocarcinoma, but the cut-off value was not evaluated [14]. An increased DOV dilutes the amylase concentration in the drainage output, which reduces the development of POPF and the consequent infection rate [14,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations